CAVA “ROYAL CITY”: AN “UNIQUE PRIVILEGE” IN THE CONSTRUCTION OF IDENTITY, BETWEEN THE MIDDLE AGES AND THE MODERN AGE. A RESEARCH APPROACH - Siani, Massimo (Journal of Tourism, Sustainability and Well-being, 2018)
In the Europe of the XV century, the administrative rules do not concern only in the cities. There are many lands, which can practice these functions. They are usually called “the other cities”, and they can either obtain or lose this identity-condition. Therefore, whichever instrument is necessary to construct and conserve them. The history of Cava, a middle town in the Kingdom of Naples (XV century), can show this by one of its most important privilege: the “White Paper”, which Ferdinando I of Aragon gave to the citizen who returned it without changes. What were the reasons? Analysing what happened in Cava’s society during the medieval (XV) and modern (XVII) age, this paper should both rebuild the historical motivations about this document and show how the role of white paper changes in relation to the construction of citizens’ identity depending on the timeline.